The High Stakes of Protecting Indigenous Homelands: Coastal First Nations' Turning Point Initiative and Environmental Groups on theB.C. West Coast - Davis, Lynne (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2009)
AbstractIn 2000, eight First Nations and the Council of the Haida Nation formed analliance to protect their traditional territories from powerful economic, politicaland ideological interests that were moving to determine the future of coastalBritish Columbia. Their organization, Coastal First Nations (formerly, the TurningPoint Initiative), has become a significant player with governments, industry andenvironmental groups in defining the parameters for transforming coastal B.C. intoa conservation-based economy, following ecosystem-based management principles.Because environmentalists initiated their Great Bear Rainforest Campaign in thehomelands of Coastal First Nations members beginning in 1995, Coastal First Nationsprovides a window into understanding the complex unfolding of relationships betweenFirst Nations and major environmental groups. Based on an analysis of interviewswith First Nations and environmental group leaders, it is proposed that theirrelationship has evolved through four phases (confrontation, relationship building,becoming allies, and shifting terrains). By speaking with one voice while respectingthe autonomy of its members, Coastal First Nations has provided a strategic vehiclefor increasing Indigenous self-determination and self-sufficiency in First Nationshomelands in the face of ongoing colonization and global forces.